On the contextualization of mathematical problems (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
In this work the treatment of the cognitive interests of students is revealed, it is a way that allows the stratification of the group students according to their tastes and aspirations, and from that position by contextualizing problems pay tribute to the work of problem solving.